Beliefs about cancer causation in Samoa: results from an awareness campaign recall survey - Beatriz Cuesta-Briand; Ernesta Sofija; Shelley Burich; Neil Harris (James Cook University, 2021)
Introduction: Cancer is a leading cause of death in Samoa. Cultural beliefs shape attitudes towards disease and disease prevention in Pacific countries, and are a barrier to engaging in cancer screening services. Methods: A survey of 205 Samoan adults conducted as part of the evaluation of the first cancer awareness campaign implemented in Samoa explored beliefs about cancer causation. Results: Lifestyle factors associated with a departure from fa'aSamoa (traditional lifestyle) were most commonly cited as causing cancer. Cancer was also attributed to pathogens and person-to-person transmission, and, to a lesser extent, cultural beliefs including supernatural agency (spirits, God). Conclusion: Addressing misconceptions while integrating certain aspects of fa'aSamoa into cancer control strategies could support greater engagement in health promotion practices and screening initiatives.